KAJIAN POLA PERKEMBANGAN KOTA BERDASARKAN PENGGUNAAN LAHAN DI KOTA PADANG - Hayati, Rahmi; Zuriyani, Elvi; Zella Putra Ulni, Arie; Juita, Erna; Nefilinda, Nefilinda; Despica, Rika (Program Studi Pendidikan Geografi Universitas PGRI Sumatera Barat, 2025)
This research aims analyzing the urban morphology of Padang City in 2010 - 2025. 2). the development pattern of Padang city. The rate of urban sprawl in Padang City. Descriptive quantitative research with a spatial approach, utilizing Geographic Information Systems. Landsat image data from 2010, 2015, 2020 and 2025 were used to identify land use change. Spatial metric analysis with Fragstats 4.2 to measure fragmentation, density, diversity of built-up areas, while Shannon's Entropy model to measure the rate of expansion. The results showed that 1). The morphology of Padang City was identified as fragmented. 2) The development pattern of built-up area shows a significant increase from 2535.94 Ha in 2010 to 55,71.72 Ha in 2025. 3) The rate of urban sprawl falls into the category of “depressed high development” with low levels of sprawl, where the growth of built-up land tends to follow a linear pattern along the road network rather than radially centralized. These findings highlight the importance of stricter RTRW implementation and integrated urban planning to manage sustainable urban growth in Padang City.